Fast Synthesis of Spherical Silica Aerogel Powders by Emulsion Polymerization from Water Glass. Issue 4 (30th January 2018) - Lee, Kyoung‐Jin; Kim, Young H.; Lee, Je K.; Hwang, Hae‐Jin
Abstract: In this study, a fast synthesis technique for silica aerogel powder was proposed that reduces the length of the tedious surface modification and solvent exchange processes. Spherical silica aerogel powder could be fabricated by an emulsion polymerization method from water glass and n‐hexane. A stable water glass‐in‐hexane emulsion with a water glass to hexane ratio of 5:5 was fabricated using the surfactant, sorbitan monooleate (Span80). It was found that acetic acid and isopropanol catalysts for the hydrolysis and condensation of water glass droplets dispersed in the emulsion were crucial for the synthesis of the spherical silica aerogel powder with a narrow particle size distribution and for reducing production time. In addition, the particle size of the spherical silica aerogel could be controlled by changing the water glass droplet size. Abstract : We prepared spherical silica aerogel powder with narrow size distribution from water glass by a fast sol‐gel synthesis technique. The silica aerogel powder could be fabricated by an emulsion polymerization method and the control of the emulsion has narrowed the particle size distribution and shortened the production time. In addition, the particle size of the spherical silica aerogel could be controlled by changing the water glass droplet size.